2008
DOI: 10.2139/ssrn.1137997
|View full text |Cite
|
Sign up to set email alerts
|

On Forecasting Daily Stock Volatility: The Role of Intraday Information and Market Conditions

Abstract: All rights reserved. Short sections of text, not to exceed two paragraphs, may be quoted without explicit permission, provided that full acknowledgement is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 71 publications
7
17
0
Order By: Relevance
“…(3) According to the comparison of the predictive power of the three types of models, the GARCH-RV model performs the better in predicting the future volatility than the GARCH-type models, which is consistent with Koopman, Fuertes et al, and Lehnert et al [6][7][8].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…(3) According to the comparison of the predictive power of the three types of models, the GARCH-RV model performs the better in predicting the future volatility than the GARCH-type models, which is consistent with Koopman, Fuertes et al, and Lehnert et al [6][7][8].…”
Section: Discussionsupporting
confidence: 74%
“…They built a GARCH-RV model and found that the GARCH-RV model has stronger predictive power than the GARCH model. Fuertes et al and Frijns et al [7,8] also showed that the GARCH-RV model has stronger power to predict the asset volatility than the GARCH model. But in realistic financial markets, the asset volatility is a continuous process with some jump components.…”
Section: Introductionmentioning
confidence: 97%
“…This is very important for investors in option markets, as an under (over)-prediction of implied volatility is more likely to be of greater concern to a seller (buyer) than a buyer (seller). The measure has been employed previously in studies evaluating volatility forecasting techniques such as Brailsford and Fa (1996) and Fuertes et al (2009).…”
Section: Mean Mixed Error (Mme)mentioning
confidence: 99%
“…There is a modeling strategy in the literature that broadly resembles this univariate approach in that AR-ARFIMA equations are fitted to time-series of daily open-to-close returns and realized volatilities computed from open-to-close intraday prices (e.g., Wu [31]; Liu and Maheu [32]; Fuertes et al [33]; Corsi et al [16]). In addition, we exploit the overnight return that is available at the market open when the forecasts are made.…”
Section: Univariate Ex Post Overnight Modeling Approachmentioning
confidence: 99%